From depression to youth school gun carrying in America: Social connectedness may help break the link - Juan, Shao-Chiu (Cogent social sciences, 2017)
School shootings are a serious US problem. Except for restricting the access to firearms, previous research has not identified mediating factors that block the pathway leading from adolescent depression to gun carrying and violence. Our examination of 1,878 adolescents in Boston public schools finds that adolescent depression is associated with carrying guns to school and that social connectedness—positive relationships between the youth and adults—may serve as a mediator between adolescent depression and taking guns to school. Parallel to gun control policy, reinforcing social connectedness may be an effective strategy to prevent mentally distressed youths from taking guns to school.